METHODOLOGICAL FOUNDATIONS OF DESIGNING A SYSTEM FOR THE DEVELOPMENT OF INFORMATION COMPETENCIES BASED ON ARTIFICIAL INTELLIGENCE (Web of Teachers: Inderscience Research, 2026)
This article examines the development of pedagogical methods that, in the wake of advances in ICT (information and communication technologies) and AI, have evolved into a holistic approach that surpasses traditional teaching methods in terms of effectiveness. The aim of the study is to provide a theoretical foundation, develop, and describe the architecture of the innovative learning method CogniSynaps, which is based on the synergy of artificial intelligence systems and immersive environments. The work is based on a systematic analysis of existing AI technologies in the field of education. The study examined the possibilities of adaptive learning, dialogic intelligent systems (AI tutoring), and multimodal pedagogy. The methodological foundation for the development of the new technology is based on the integration of an intelligent adaptive e-learning system (AES) that encompasses diagnostic (KNN algorithms), generative (LLM models), simulative (sandbox environments), and analytical (NLP technologies) and is coupled with extended reality (XR) technologies.